Peran insulin-resisten dan hiperinsulinemia dalam etiologi hipertensi esensial - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
. .The association between hypertension and diabetes mellitus is well recognized. Several reasons for the coexistence of these disorders have been postulated, i.e. as part of aging process, diabetes causes macrovascular and microvascular disease, renovascular stenosis which is enhanced by the development of hypertension. Insulin causes renal sodium reabsorption, stimulates the sympathetic nervous system, increases intracellular calcium, and is a vascular growth factor. The paper described a short review of a new dimension in hypertension, that is the role of insulin resistance in the pathogenesis of essential hypertension which is common in diabetes mellitus. This in turn opens a new dimension of potentially more selective drug therapy to combat hypertension and associated risk factors.